Intensifications of the wooling mechanism with increasing electric conductivity of fibers - Khasanov Doston (Academia Open, 2019)
The wide possibilities of modifying manufactured industrial fibers aimed at improving their physico-mechanical properties, structural and technological parameters. In connection with the above, it was of interest to study the effect of a number of water-soluble compositions based on a poly-quaternary salt of dimethyl-allyl-β - methacryloyloxyethylammonium bromide in combination with glycerin on the structural and physico-mechanical properties of protein fiber, and also to study the effect of the composition on wool spinning and the quality of wool yarn .